Effect of zeolitic imidazolate framework-8 and multi-walled carbon nanotube on the performance of pvdf membrane - Nurul Hazreen Wanie, Hazmo (2020)
The main concern in membrane technology is the membrane fouling, which occurs during the filtration process, causing a reduction in water flux and deteriorates the stable performances of membrane filtration system. Several approaches were introduced to eliminate the organic fouling including the incorporation of nanoparticles into a polymer membrane such as silver nanoparticles (AgNPs), zinc oxide (ZnO), zeolitic imidazolate frameworks (ZIFs) and carbon nanotubes (CNTs). Therefore, the synthesized zeolitic imidazolate framework 8 (ZIF-8) and multi-walled carbon nanotubes (MWCNTs) were used as inorganic additives in this work with composition of 0.1wt.%, 0.3wt.% and 0.5wt.%, respectively. The preparation of polyvinyldifluoride (PVDF) membranes was done via physical blending method. The prepared membranes were then characterized by using scanning electron microscopy (SEM), energy dispersive x-ray spectrometry (EDX), and contact angle analysis to investigate their structures in terms of morphology and hydrophilicity properties. Water permeability and filtration performance test were performed using pure water, bovine serum albumin (BSA) and humic acid (HA) solution to evaluate the fouling resistance of the prepared membranes. Even though the fluxes decreased over time, it was found that the ZIF-8/PVDF membrane with 0.5 wt.% concentration has the highest percentage of solute rejection for both BSA (>92%) and HA (>94%) solution as compared to MWCNT/PVDF membranes and pure PVDF membrane. Overall, the nanocomposite membranes showed an improvement in the hydrophilicity, permeability, and solutes rejection rate compared to pristine PVDF membrane. The anti-fouling properties of nanocomposite membranes also has been enhanced with higher flux recovery rate values and lower flux decline rate were achieved as compared to pristine PVDF membrane.